PERTIMBANGAN HAKIM MENJATUHKAN PUTUSAN PERKARA NARKOTIKA DALAM PUTUSAN 100/PID.SUS/2023/PN. IDI - Nainggolan, Khairina Putri; Aldyan, Arsyad (Sebelas Maret University, 2026)
This article analyzes the legal considerations used by judges in issuing criminal sentences for narcotics cases based on Decision Number 100/Pid.Sus/2023/PN Idi. The purpose of this study is to evaluate the suitability of the judge's considerations in the decision with the suitability regulated in Article 183 of the Criminal Procedure Code (KUHAP). This study uses a normative legal research method with a case study approach, which focuses on the analysis of the suitability of Article 183 of the Criminal Procedure Code as a reference for the evidentiary system in criminal law. Based on the results of the study, it was found that the judge's considerations in deciding narcotics criminal cases were in accordance with the theory of evidence (bewijstheorie) and met the requirements specified in Article 183 of the Criminal Procedure Code. The judge considered at least two valid pieces of evidence, namely witness statements, the defendant's statement, and evidence presented at trial. These considerations gave the judge confidence that the defendant was proven to have no right to control Class I narcotics, not plants.